Sosialisasi Penerapan Metode Arima Untuk Peramalan Permintaan dan MRP untuk Perencanaan Bahan Baku Pengemasan Minyak Goreng - Sesaria Maharani Rachma P; Sita Aniisah Sholihah; Wahyu Poncotoyo; Andy Maulana; Jonathan Jonathan (Institut Transportasi dan Logistik Trisakti, 2023)
One of the important supply chains that supply raw materials for edible oils is the production system. Influencing costs that can be minimized by preventing overstocking of raw materials. The purpose of this activity is to explain the importance of supply chain inventory planning in food ingredients and to estimate demand using forecasting techniques, i.e. production planning using Autoregressive Integrated Moving Average (ARIMA) and Material Requirements Planning (MRP). to carry out the plan. Method based on Fixed Order Quantity (FOQ) and Periodic Order Quantity (POQ). This activity is targeted at food distributors, and it is expected that the effectiveness and efficiency of food distribution activities will be enhanced by applying these two methods. The socialization method is conducted through webinars (online seminars) with presentations of materials and questions and answers. There were 104 seminar participants, consisting of employees from various production and logistics institutions and 4 ITL Trisakti lecturers. According to the evaluation questionnaire after the exchange meeting, the seminar participants were satisfied and interested in the activities of her ITL Trisakti Lecturer. The results of this socialization activity will be very useful for the training of industry participants, especially those working in the food sector.